Dual‐Ion Flux Management for Stable High Areal Capacity Lithium–Sulfur Batteries. Issue 10 (27th January 2022) - Liu, Borui; Torres, Juan F.; Taheri, Mahdiar; Xiong, Pan; Lu, Teng; Zhu, Junwu; Liu, Yun; Yu, Guihua; Tricoli, Antonio
Abstract: Controlling the interaction between multiple ion fluxes is a major challenge that hampers the adoption of post‐Li intercalation battery systems, which offer a multifold increase in energy density over existing technologies. Here, a dual‐ion flux management strategy is introduced to simultaneously control the distribution of Li and polysulfide ions in high‐energy Li–S batteries. This approach enables long‐term use of high S‐loading cathodes with 13.6 mgsulfur cm −2, achieving 9 mAh cm −2 areal capacity with 73% capacity retention for 1000 charging/discharging cycles. The battery system relies on the use of a multiscale membrane, with comparable size to existing battery separators, which simultaneously acts as an atomic redisperser for Li ions, dielectric and mechanical separator, polysulfide barrier, and extended cathode. Combined characterization and modeling reveal that the membrane is stable down to <1.0 V versus Li + /Li and result in a uniform Li‐ion flux to the anode and effective polysulfide confinement and reutilization. The potential of this approach for application is demonstrated by the fabrication of stable pouch cells with a horizontal surface of 40 cm 2 and 6.8 mAh cm −2 capacity. These findings provide an exemplification of the potential for effective multi‐ion flux management for future energy storage and emerging electrochemical systems. Abstract : Engineering solutions for stabilizing Li–S batteries currently face a dilemma. Polysulfide shuttling results in rapid capacity loss, while the absence of polysulfides on the Li‐anode promotes Li dendrite formation if this shuttling is completely blocked. A dual‐ion management strategy for stabilizing of both electrodes can simultaneously elevate the sulfur loading, charge–discharge efficiency, and cycle life for Li–S batteries.